Fabrication of catalytic ceramic membrane in hybrid catalytic oxidation filtration process for water treatment - Liangdy, Arvin (Nanyang Technological University, 2025)
The presence of emerging organic micropollutants (MPs), such as antibiotics, pesticides and pharmaceutical products is widespread due to their extensive use in medicine, industry, agriculture, and daily human consumption. Despite their typically low concentrations and shorter half-lives compared to persistent organic pollutants, MPs pose significant risks by contaminating aquatic ecosystems and potentially leaching into drinking water sources due to their emissions, biological toxicity, and propensity for bioaccumulation. Their classification as potential carcinogens and endocrine disruptor underscores the urgent need for efficient wastewater treatment solutions. The integration of advanced oxidation processes (AOPs) with catalytic ceramic membranes (CCMs) offers a promising approach to enhance organic matter removal in water treatment while reducing membrane fouling. The use of CCM in the hybrid process intensifies the organic pollutants degradation and mineralization, but its practical application faces challenges such as limited catalytic activity, the formation of toxic by-products and sensitivity to water matrices. This thesis work aims to address these limitations and improve the removal efficiency in the hybrid process by developing CCMs with enhanced catalytic activity, versatility in various oxidant activation and reduced interference from background species. The use of bimetallic oxides (e.g., Co-Mn) enhances the activation of oxidants, generating stronger reactive oxygen species (ROS) that efficiently degrade MPs and facilitate the mineralization of their by-products, significantly reducing post-treatment toxicity. The incorporation of Fe₃O₄ enables the CCM to activate different oxidants, including peroxymonosulfate (PMS), peroxydisulfate (PDS), and the Fenton process (H₂O₂). This broadens the range of oxidants to be activated and MPs that can be degraded. Furthermore, the catalytic active layer on the CCM surface minimizes interference from water matrices by selectively rejecting background components, allowing only micropollutants to permeate and undergo degradation within the CCM substrate, thus ensuring efficient ROS utilization. This research involved the development and evaluation of various CCMs, including a Co-Mn bimetallic oxide impregnated CCM (CoMn₂O₄-CCM) fabricated via a citrate-acid wet impregnation method, which demonstrated superior sulfamethoxazole (SMX) removal in continuous flow experiments due to enhanced redox cycling (Chapter 3). The CCM was effective in removing 99% SMX within hydraulic retention time (HRT) of 13.7 s, achieving a low specific oxidant consumption of 1.2 M PMS M-1 TOC. The investigation highlighted the critical role of process parameters in optimizing the CCM/PMS system's performance. The ratio between catalyst loading in CCM, oxidant concentration and pollutant concentration influenced the availability of active sites on the catalyst to activate oxidants in the process and the possibility of self-scavenging of the generated reactive oxidizing species (ROS). Fe₃O₄-impregnated CCM, developed using a facile ethylene-glycol gel method, showed effective atrazine (ATZ) removal across different AOPs and water matrices, such as settled water and RO retentate (Chapter 4). The resulting Fe3O4-CCM efficiently activated peroxymonosulfate (PMS) to generate reactive oxygen species (ROS), achieving a 99% removal of atrazine (ATZ) within a short hydraulic retention time (HRT) of 5.7 s. The versatile Fe3O4-CCM could also effectively activate H2O2 and peroxydisulfate (PDS). It demonstrated robustness in real wastewater matrices (settled water and RO-reject) collected from local water reclamation and treatment plants and in presence of humic acid. Moreover, a CCM with a Co₃O₄ impregnated layer and a TiO₂-coated surface demonstrated enhanced acetaminophen (ACT) degradation with minimized interference from organic matter in real water samples (Chapter 5). The CCMs effectively activated peroxymonosulfate (PMS), achieving ACT degradation of 85% and 93% in real water matrices (reverse osmosis retentate and settled water, respectively) and 99% in MQ water. The CCMs demonstrated consistent performance across multiple operational cycles, even in the presence of humic acid (HA) (96% ACT reduction). The study identified by-products formed during the degradation process and analyzed their toxicity, revealing a significant reduction in post-treatment toxicity. It also explored degradation pathways involving both radical and non-radical mechanisms, identifying radical pathway reactive oxygen species (ROS) such as SO₄•⁻, •OH, O₂•⁻, as well as non-radical pathways like ¹O₂, electron transfer mechanisms. The mechanistic study provided insights into the optimal conditions for each pathway. The CCMs also demonstrated effective degradation of micropollutants in the presence of background species such as anions and humic acid and exhibited good performance when tested with real water samples. Furthermore, the CCMs showed good reusability and long-term performance, confirming their potential for practical and sustainable operation in real-world water treatment scenarios. Furthermore, the reusability and long-term performance of the CCMs were evaluated, demonstrating their potential for practical and sustainable operation in real water treatment scenarios. Overall, this research provides a novel and effective solution for tackling the challenge of emerging micropollutants in water treatment. The advanced CCM-AOP hybrid systems developed here can be applied to diverse water matrices, offering a scalable and adaptable approach for municipal and industrial wastewater treatment facilities. These findings contribute to safer water management practices by enhancing the degradation of harmful contaminants, minimizing toxic by-products, and offering a pathway toward cleaner, safer drinking water and a more sustainable water purification process.